2016
DOI: 10.1002/per.2059
|View full text |Cite
|
Sign up to set email alerts
|

Trait Intellect Predicts Cognitive Engagement: Evidence from a Resource Allocation Perspective

Abstract: Trait Intellect, one of the two 'aspects' of the broader Openness/Intellect 'domain', predicts performance on a range of cognitive tasks including tests of intelligence and working memory. This has been explained in terms of the tendency for high-Intellect individuals to explore, or engage more effortfully with, abstract information. This theoretical perspective can be framed in the language of Resource Allocation Theory, in terms of high-Intellect individuals allocating more of their available cognitive resou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 58 publications
3
21
0
Order By: Relevance
“…Experimental findings (Smillie et al, 2016) support the assumption that intellect covers both seek and conquer processes. These authors found a positive relation of intellect and task performance variables and emphasize the utility of high intellect for learning and performance.…”
Section: Introductionsupporting
confidence: 68%
“…Experimental findings (Smillie et al, 2016) support the assumption that intellect covers both seek and conquer processes. These authors found a positive relation of intellect and task performance variables and emphasize the utility of high intellect for learning and performance.…”
Section: Introductionsupporting
confidence: 68%
“…Industriousness (partialling Orderliness), Openness, and Intellect appear to be robust predictors of components of work engagement (vigor, dedication, and absorption;Bakker, Schaufeli, Leiter, & Taris, 2008;Douglas, Bore, & Munro, 2016;Woods & Sofat, 2013). Intellect (distinct from Openness) also predicts more effortful cognitive engagement during a difficult cognitive task (Smillie, Varsavsky, Avery, & Perry, 2016), whereas Openness (distinct from Intellect) has been linked with deeper engagement in abstract art (Fayn, Tiliopoulos, & MacCann, 2015).…”
Section: Personality Traits and (P)erma Well-beingmentioning
confidence: 95%
“…Industriousness (partialing Orderliness), Openness, and Intellect appear to be robust predictors of components of work engagement (vigor, dedication, and absorption; Bakker, Schaufeli, Leiter, & Taris, ; Douglas, Bore, & Munro, ; Woods & Sofat, ). Intellect (distinct from Openness) also predicts more effortful cognitive engagement during a difficult cognitive task (Smillie, Varsavsky, Avery, & Perry, ), whereas Openness (distinct from Intellect) has been linked with deeper engagement in abstract art (Fayn, Tiliopoulos, & MacCann, ).…”
Section: Personality Traits and Three Taxonomies Of Well‐beingmentioning
confidence: 99%